2009
DOI: 10.1182/blood.v114.22.4042.4042
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Ago2 Complex in Mature Human Red Blood Cells.

Abstract: 4042 Poster Board III-977 Background MicroRNA (miRNA) is noncoding short RNA which plays important roles for cell death, proliferation, development and differentiation. MiRNA binds to 3' UTR region of target messenger RNA(mRNA), and negatively regulates gene expressions by inducing instability of mRNAs or translation block. This function of miRNA depends on the presence of cytoplasmic protein complex, RNA induced silencing complex(RISC). A main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Experiments using Zebra fishes showed knockout of miRNA-451 induced severe reduction of RBC production, suggesting that miRNA 451 is one of the key molecules for erythropoiesis. One study suggested that miRN-451-Ago2 complexes in mature RBCs may be playing roles for homeostasis of normal erythropoiesis, and the analysis of miRNAs-Ago2 complex in RBCs is relevant for understanding normal and pathological erythropoiesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using Zebra fishes showed knockout of miRNA-451 induced severe reduction of RBC production, suggesting that miRNA 451 is one of the key molecules for erythropoiesis. One study suggested that miRN-451-Ago2 complexes in mature RBCs may be playing roles for homeostasis of normal erythropoiesis, and the analysis of miRNAs-Ago2 complex in RBCs is relevant for understanding normal and pathological erythropoiesis [22].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this belief, we and other groups have discovered that human erythrocytes actually contain abundant and diverse species of micro-RNAs and other transcripts that persist beyond terminal differentiation. 14,15,[16][17][18][19][20] While the initial focus was on micro-RNAs in mature erythrocytes, 14,20 RNA-Seq has further revealed that mature erythrocytes have a large number of largesized RNAs, including mRNAs and non-coding RNAs. 21 The functional relevance of these erythrocyte transcripts has been summarized in a recent review.…”
Section: Discovery Of Micrornas In Human Erythrocytesmentioning
confidence: 99%